Gendered perceptions of tigers in Chitwan National Park, Nepal. (October 2016) - Carter, Neil H.; Allendorf, Teri D.
Abstract: The survival of many populations of threatened mammals depends on the willingness of human communities to coexist with them. Gender is an important factor because men and women often have different perceptions of wildlife that influence their willingness to coexist with wildlife. While previous studies have hypothesized what may drive gendered perceptions of wildlife, research investigating the underlying drivers of these differences is lacking, especially in developing countries. The objective of this paper is to identify the underlying drivers of gendered differences in attitude toward globally endangered tigers ( Panthera tigris ) in Chitwan National Park (CNP), Nepal, where women are less likely to have a positive attitude. To accomplish this, we administered a social survey to 499 respondents living near the park. We analyzed survey data using nested linear regression models and decomposition analysis. Over 90% of the gender gap in attitude was explained through these analyses, with beliefs about tigers (e.g., benefits and costs) explaining two-thirds of the gap. The belief that tigers contribute to a healthy forest, by itself, accounted for one-third of the gender gap. Socio-economic characteristics explained 12% and experiences with tigers and perceptions of and control over risk each accounted for 6% or less of the gender gap. These results suggest that beliefs, rather than socio-economics, experience, or risk, underlie the majority of the gendered differences in attitudes toward tigers in CNP and that an appreciation of the ecosystem value of tigers plays a key role in people's positive attitudes. Analyses of gendered differences in attitudes are important for developing conservation interventions that address perspectives and issues of the entire population. Highlights: We explored drivers of gendered differences in attitude toward tiger. Using decomposition analysis, we explained 94% of the gender gap in attitudes. Beliefs about tiger accounted for two-thirds of the difference in attitudes. Belief that tigers keep the forest healthy explained one-third of the attitude gap.